The gut microbiota of Indigenous populations in the context of dietary westernization: a systematic review and meta-analysis - Daunizeau, Camille; Franck, Maximilien; Boutin, Amélie; Ruel, Marianne; Poliakova, Natalia; Ayotte, Pierre; Bélanger, Richard (Frontiers in Nutrition, 2025)
BackgroundIndigenous populations worldwide are undergoing dietary transitions from traditional patterns toward westernized diets, influencing gut microbiota diversity and composition, with potential implications for health.ObjectiveThis systematic review and meta-analysis aimed to compare gut microbiota diversity and composition among Indigenous populations following traditional versus westernized dietary patterns.MethodsA comprehensive literature search was conducted in March 2024 and updated on February 25, 2025 across databases, including All Ovid MEDLINE®, Embase, Web of Science, CAB Abstracts, and Food Science and Technology Abstracts, along with searches of gray literature sources. Eligibility criteria included observational studies comparing gut microbiota diversity and composition between traditional and westernized diets among healthy Indigenous adults (≥16 years) without chronic diseases. Two reviewers independently performed study selection, data extraction, and risk of bias assessment using the ROBINS-E tool. Data were synthesized using random effects models, specifically applying the restricted maximum likelihood estimator to calculate between-study variance (τ2).ResultsOf 19,836 articles identified, nine studies (N = 657 participants) met inclusion criteria. Traditional diets tended to be associated with higher microbial diversity, although results varied across diversity metrics and studies. Shannon diversity was higher in traditional groups, but this difference was not statistically significant (standardized mean differences = 0.67; 95% CI: −0.26 to 1.60; I2 = 92.9%). Other diversity indices (Chao1, Simpson, observed species richness) did not show clear differences between diet groups. Descriptive taxonomic analyses also revealed substantial heterogeneity across populations, reflecting the context-specificity of microbiota differences between traditional and westernized groups. Nonetheless, most westernized groups exhibited a higher Firmicutes/Bacteroidetes ratio at the phylum level and a lower Prevotella/Bacteroides ratio at the genus level.ConclusionThe observed heterogeneity likely reflects methodological differences, ecological variability, and the diversity of traditional diets and varying patterns of dietary transition. Longitudinal research is needed to better understand how dietary transitions affect gut microbiota over time in Indigenous populations.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024597804.